ISOLATION AND PURITY DNA FROM LEAF STORAGE OF Lansium domesticum CORRESPOND FOR BARCODING ANALYSIS - Nur Arifah; Laila Hanum; Sarno Sarno; Nita Aminasih; Singgih Tri Wardana; Hary Widjajanti (BIOVALENTIA: Biological Research Journal, 2023)
Lansium domesticum is one of tropical plant. Genetic studies of tropical plant species occurred very slowly due to some obstacles. Provided fresh sample for isolation step was one of impediment. Fresh sample was important conditions to avoid impure DNA template. A simple and rapid technique was needed to get a pure DNA from storage sample. The aims of this study is to see the purity of the DNA isolation results from Lansium domesti-cum mature leaf from South Sumatra that have been stored for 2 years and to test whether the DNA isolation results can be used for barcoding analysis by amplification using PCR method with rbcL primer. There are 11 sample of Lansium domesticum were taken from 8 districts in South Sumatra. The sample was the mature leaves of Lanisum domesticum. The leaves were stored in a freezer at -20oC for two years. There was one sam-ple stored within 2 weeks as a comparison. The results of the study showed the isolation of DNA from storage and mature leaves of Lansium domesticum used Plant Genomic DNA Kit DP305 had a good quantity for 7 sample. 3 sample had low purity and 1 sample contaminated by RNA.  Despite electrophoresis showed the isola-tion result not intact and compact, nevertheless the PCR results showed 11 samples could be amplified using rbcL primer. This result indicated the DNA isolation method suit for barcoding analysis using PCR method.